THE INFLUENCE OF “CRUELLA” MOVIE TO IMPROVE STUDENTS’ VOCABULARY, A CASE OF XI GRADE STUDENTS’ MAN 1 BREBES IN THE ACADEMIC YEAR 2022/2023 - Annisa Salmawati (Berajah Journal, 2022)
This study was based on the fact that there are still many students who have not mastered the vocabulary correctly, and only a few students have mastered the vocabulary. The study aims to determine how much the "Cruella" film contributrd to students' vocabulary knowledge and how their reactions to the film affected their ability to master new words. This type of research is called "experimental research" with participated by 26 students. Quantitative design was used as the research method in this study. The term “experimental research” describes the type of study in which 26 students participated. Pre-experimental design with a One-Group Pretest-Postest type was used in this research, and pre-and post-test were used to collect the data. The t-test statistic was utilized with a significant level of alpha 0.05 for outcome. The procedure produced a t_score > t_table is 20,23 > 1,70, showing H_1 was approved. The researcher concluded that “Cruella” film helped students in MAN 1 Brebes learn more vocabulary. Furthermore, the student response to questionnaire on the usage of the media “Cruella” movie was very positive, and they appeared excited, calm, and comfortable when learning and during the learning process.